Tunable photoluminescence of CaCu3Ti4O12 based ceramics modified with tungsten - Moreno, H. [UNESP]; Cortes, J. A. [UNESP]; Praxedes, F. M. [UNESP]; Freitas, S. M.; Rezende, M. V. S.; Simoes, A. Z. [UNESP]; Teixeira, V. C.; Ramirez, M. A. [UNESP] (Elsevier B.V., 2021)
CaCu3Ti4O12 (CCTO): x% W (x = 0.00, 0.02, 0.05, 0.10, 2.50, and 5.00) powders were prepared via solid-state reaction. The effect of W addition in the (micro)structure and optical properties was analyzed using computing simulations and experimental techniques. The widespread application of perovskite-lightemitting diodes (PeLED5), photovoltaic devices, and photocatalysis is limited by the intrinsic instability of the perovskite materials (e.g., metal halides), compromising operational efficiency, and pushing for the development of novel perovskite materials. The Rietveld analysis and XPS results confirm the presence of W5+, Ti3+, and Cu+ ions in all samples of the CaCu3Ti4O12 : x% W system, leading to structural changes that strongly influence the PL response of the material. Based on a correlation approach, a practical model explaining the relationship between electronic defects and photoluminescent (PL) emissions in the CCTO system is proposed. On samples x = 0.00, 0.10, and 5.00, red PL emissions are due to the presence of metal vacancies, and deep-level defects, while blue PL emissions on samples x = 0.02, 0.05, and 2.50 are associated with shallow defects. Thus, our research shows evidence that CaCu3Ti4O12 (CCTO): W ceramic systems may be promising to photonics applications. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: CaCu3Ti4O12; X-ray absorption; Photoluminescence; Atomistic modeling